A very intimate takeover - LaQuette (LaQuette. Devereaux Inc., 2021)
"Trey Devereaux is out to prove her corporate mettle to her skeptical father. When she sees a chance to take control of Devereaux Inc. from her estranged grandfather, she pounces. But Jeremiah Benton, his second-in-command, is fiercely protective of the Devereaux patriarch--and absolutely enticing. The intensity of their attraction overwhelms her defenses, and Trey even finds herself warming to her grandfather under Jeremiah's influence. Can Trey maintain her resolve--or is Jeremiah winning this high-stakes merger? The fate of a billion-dollar Brooklyn legacy lies in the balance"--